Body image and acceptance of cosmetic surgery in China and the Netherlands: A qualitative study on cultural differences and similarities. (March 2022) - Wu, Yi; Mulkens, Sandra; Alleva, Jessica M.
Highlights: Chinese and Dutch women describe in interviews similar views about cosmetic surgery. Women described sociocultural, intrapersonal, and benefit factors as pro surgery. Reasons against cosmetic surgery included intrapersonal and risk factors. Socioeconomic benefits of female beauty were more salient among Chinese women. Cross-cultural differences in conceptualizing body appreciation were identified. Abstract: There is an established relationship between acceptance of cosmetic surgery and psychological factors, including body image. However, qualitative research among diverse cultural groups is needed to provide a more fine-grained understanding of the influences on women's attitudes towards cosmetic surgery. In this study, 20 Chinese and 20 Dutch women aged 18-50 years ( M Chinese = 34.20; M Dutch = 34.70) participated in one-on-one semi-structured interviews. Data were analyzed using reflexive thematic analysis. We identified three themes that captured the factors that women perceived to foster favorable attitudes towards cosmetic surgery: (a) sociocultural pressures (e.g., normalization of cosmetic surgery, appearance-focused peers); (b) intrapersonal characteristics (e.g., beauty-ideal internalization, social comparison); and (c) benefits of beauty (e.g., attracting men, socioeconomic benefits). Conversely, two themes captured the factors perceived to reduce favorable attitudes towards cosmetic surgery: (a) intrapersonal characteristics (e.g., unconditional body acceptance, self-confidence); and (b) external considerations (e.g., health risks, financial costs). Overall, Chinese and Dutch participants shared many similarities in their opinions about what might affect cosmetic surgery consideration. The most striking cross-cultural differences concerned perceived socioeconomic benefits of beauty (mainly Chinese women) and women's conceptualization of body appreciation. This study may enable a more comprehensive understanding about the factors influencing Chinese and Dutch women's attitudes towards cosmetic surgery, and the nuances in these relationships across these cultures.